Anteseden Pembelian Impulsif Produk Fashion oleh Pria (Studi pada Toko Ritel Fashion di Jakarta) - Munawaroh, Nuril Aulia; Rohman, Fatchur (Universitas Brawijaya, Indonesia, 2014)
This study aims to explore the factors that consisting of perceived stimulation, perceived crowding, fashion involvement, credit card usage and employee assistance that affecting men in Jakarta buying fashion products impulsively. The research population is all man in Jakarta who have credit cards and doing fashion products impulse buying in fashion retail stores in Jakarta, where the amount is limited, so the researchers used the Bentler and Chou formulas that produce as much as 145 respondents. The sampling method was done by using accidental sampling method based on chance, in the sense of a man who is doing impulse buying fashion products. Hypothesis testing was done by structural equation analysis (Structured Equation Model) with AMOS (Analysis of Moment Structure) application. The results showed that (1) perceived stimulation has a positive and significant impact on impulse buying fashion products by men in Jakarta, (2) perceived crowding positively but not significantly affect men in Jakarta doing impulse buying fashion products, (3) perceived crowding positively but does not affect the employee assistance of fashion retail store (4) employee assistance positively and significantly affects men in Jakarta doing impulse buying fashion products, (5) fashion involvement positively and significantly affects men in Jakarta doing impulse buying fashion products, (6) credit card usage positively and significantly affects men in Jakarta doing impulse buying fashion products, (7) employee assistance is positive but as moderating variables did not significantly affect men in Jakarta impulsive purchases. The retailers are advised to maintain indicators of the store environment and service performance shop that has been assessed and improved performance indicators have not been assessed either by the customer. It is expected to increase customer convenience while shopping so as to encourage impulse buying.